Cultures in translation, complexity and development inequalities: cultivating spaces for shared understanding. (2nd January 2021) - Woodin, Jane; Hamaidia, Lena; Methven, Sarah
ABSTRACT: This article argues that complex and multi-perspective approaches to translation and intercultural studies are necessary in order to address the Sustainable Development Goals, whose overall aim is 'leave no-one behind'. Taking examples from international development project experiences, we consider the role of 'translating cultures' in these fluid exchange spaces of multilingual and intercultural encounters, particularly at project beneficiary level where there is significant inequality and power difference between different actors. Development projects often focus on efficiency at the expense of inclusion; we emphasise the need to open up linguistic and cultural spaces to allow the interrogation of values and processes.